Rainwater Harvesting Potential for Targhadia Watershed (Rajkot, Gujarat, India) - Khandelwal, M K; Shakya, S K; Narda, N K; Khepar, S D (Journal of Agricultural Engineering, 2004)
In the present study, an attempt was made to scientifically analyze rainfall and runoff data for period of 1971-97 and 1975-97 respectively collected from Targhadia watershed (Rajkot) with relevant statistical tools. Regression of potential evaporation and potential evapotranspiration on observed pan evaporation has been adequately studied for the region. Generation of harnessable water yield based on the different models namely NPB model, USDA SCS CN method and SWMHMS have been thoroughly studied for the study area. The modified SWMHMS model and the USDA SCS CN method yielded results better than NPB model for the entire period of 1975-97 period.